Pemberdayaan Masyarakat melalui Pengolahan Jambu Merah Delima (Syzygium semarangense) di Kabupaten Demak - Wiludjeng Roessali; Priyo Sasmoko; . Darwanto (Institut Pertanian Bogor, 2017)
Community service activities through science and technology for society program in the Mranak Village, Wonosalam Subdistrict, Demak District directed to empower the community to generate additional income for the family through the application of technology processing fruit and business development. The method used was training and production practices that were preceded by Focus Group Discussion (FGD) to plan for business groups and marketing strategies. Program participants were members of the PKK Mranak Village and women farmers group Mutiara Tani (Gapoktan). Results of empowerment through training and practice showed positive response of the participants. Pioneering to business groups performed through the marketing of products in environmental assessment activities in some places in the Semarang City. Product jam and pie based on organoleptic test can be accepted by the market. Application of marketing strategy and better organization of production that will be initiated the establishment of joint venture group. This empowerment program in the long term is expected to be a thriving business with the capacity and better quality.